Dopamine adsorption configurations on anatase (101) surface - Stashans, A. (2015)
Present work is based on the density functional theory (DFT) and generalized gradient approximation studies. Different adsorption geometries of dopamine, C8H11O2N, on the anatase (101) surface have been considered and carefully investigated. Bidentate chelating configuration with two molecular oxygens binding to the same surface titanium has been found to be the equilibrium case. The Ti-O distances for this configuration are obtained to be equal to 2.23 and 2.37 , respectively. © 2015 World Scientific Publishing Company.